Historical and recent tomato black ring virus and beet ringspot virus isolate genomes reveal interspecies recombination and plant health regulation inconsistencies. (18th November 2021) - Fowkes, Aimee; Adams, Ian P.; Jones, Roger A. C.; Fox, Adrian; McGreig, Sam; Boonham, Neil
Abstract: Tomato black ring virus (TBRV) and beet ringspot virus (BRSV) are closely related but distinct members of subgroup B of the genus Nepovirus . Both viruses have broad host ranges and are transmitted by seed, pollen, and ectoparasitic nematodes. Although 13 TBRV and 3 BRSV genome sequences were already available, no attempt has been made to link sequence data from these recent sequences with those of historical isolates studied in the pre‐sequencing era. High‐throughput sequencing was used to generate eight new TBRV and BRSV genome sequences from three historical >60‐year‐old and two >30‐year‐old isolates, and three more recent isolates. These eight isolates were from the Czech Republic, Germany, and the UK. We compared these with all genomes sequenced previously. Intraspecies recombination (three of four TBRV and two of four BRSV isolates) was frequent amongst the eight new genomes. Interspecies recombination was also present within the RNA1 of TBRV isolates BRSV‐3393 SG GB and BRSV‐9888 ST GB. No satellite RNAs were associated with the eight new genomes. Two commercial enzyme‐linked immunosorbent assay (ELISA) kits used to detect TBRV during routine testing differed in that one detected only TBRV and the other only BRSV, so they are likely to provide incorrect but potentially complementary virus occurrence information. We suggest both ELISA kits, or appropriate molecular tests, be used by biosecurity authorities to avoid this problem. This study illustrates the value of sequencing historical isolates preserved from the pre‐sequencing era. Abstract : Testing contemporary and historical tomato black ring virus and beet ringspot virus isolates gave information on phylogenetics, recombination, and diagnostic information on commercial enzyme‐linked immunosorbent assay kits.